Access to child care services in the Northeast and in the South Regions of Brazil - Andréia Soprani dos Santos; Suele Manjourany Siva Duro; Nagela Valadão Cade; Luiz Augusto Fachini; Elaine Tomasi
Abstract Objectives: to estimate the incomplete follow-up on child care services and the associated factors in the municipalities in the Northeast and in the South of Brazil. Methods: a population-based cross-sectional study with 7,915 children. The incomplete follow-up on child care regarded the absence of at least one of the seven advocated care services. The Poisson regression was used for crude and adjusted analysis. Results: the prevalence of the incomplete follow-up child care was 53.6% (CI95%= 52.5-54.7) in the Northeast and 28.3% (CI95%= 27.3-29.3) in the South, therefore 91% was greater in the Northeast (PR=1.91; CI95%= 1.73-2.11). Protector effect was observed: in the muni-cipalities with 30 to 49 thousand inhabitants in the Northeast (PR= 0.72; CI95%= 0.64-0.82) and 100 to 999 thousand inhabitants in the South (PR=0.69; CI95%= 0.57-0.84); the South has the greatest income quartile (RP=0.77; CI95%= 0.63-0.95) and has six or more prenatal consultations (PR=0.83; CI95%= 0.75-0.92) in the Northeast and (PR=0.65; CI95%= 0.53-0.79) in the South. Social classes D and E showed risks (PR=1.41; CI95%= 1.19-1.67) in the Northeast and (PR=1.67; CI95%= 1.37-2.03) in the South. Conclusions: children in the Northeast are more likely not to have a complete child care follow-up, implying that the user does not come to be attended or finds difficulties to have access to the health services.